THE INFLUENCE OF SERVICE QUALITY, PRICE AND BRAND IMAGE ON TELKOMSEL CUSTOMER LOYALTY OF IPB POSTGRADUATE STUDENTS - Afra Nazhirah; Annisa Rizki Khairan; Mukhamad Najib (Journal of Business Studies and Management Review, 2020)
The study aims to find out how the influence of service quality, price, and brand image on Telkomsel customer loyalty for IPB postgraduate students and to find out what the most influential variable on customer loyalty. This study used 95 students of IPB Postgraduate who have used The Telkomsel Card in The Jabodetabek area and in the last 2 months. This study used non-probability sampling technique with judgmental sampling. The data were collected by online questionner with a Likert scale between 1 to 5. The multiple linear regression analysis was used to test the model. The data processing of this study used SPSS 24.0. The result of this study with F test has shown that the service quality, price, and brand image simultaneously can explain the variable of customer loyalty. The next result with the T test has shown that price has a positive and significant effect on customer loyalty.